The Effect Of Four Square Step Excercise On The Risk Of Falling Elderly At Pstw Wana Seraya Denpasar 2019 - Desak Gede Nanda Amaria Dewi; Sang Ayu Ketut Candrawati; Ni Kadek Muliawati (Alma Ata University Press, 2020)
Elderly undergoes various changes due to the aging process, one of them is the musculoskeletal system which results in the elderly being vulnerable to falls and if not be treated, it can cause injury to the elderly and even death. One way to reduce the level of fall risk in elderly is to do balance exercises, especially four square step exercises which is not only train the muscle strength of elderly but also train the visual coordination. The purpose of this study was to determine the effect of four square step exercises on the fall risk in elderly. This study used a design of pre-experimental one group pre-test and post-test without control group. The study was conducted at PSTW Wana Seraya Denpasar. The respondens in this study selected through purposive sampling technique. Among 36 elderly who living at PSTW Wana Seraya Denpasar, there were 17 people who met the inclusion and exclusion criteria. After calculating the sample, there were 15 samples were obtained. The results of the study, the fall risk in elderly before four square step exercise were 12 respondents (80%) at moderate level and three respondents (20%) at high level. After training, nine respondents (60%) had a moderate fall risk and six respondents (40%) had low fall risk. Based on the results of Wilcoxon signed rank test statistical test, it was obtained p value = 0.003 <α 0.005 which means there is an influence of four square step exercises towards the fall risk in elderly. Based on the results of the study, the four square step exercise is an effective exercise to reduce the fall risk in elderly because it is a light exercise which is easily carried out by the elderly independently. This exercise is recommended to be applied as a method to reduce the fall risk in elderly.